Effect of extending hot weather periods on approach to floor construction in moderate climate residential buildings = Wpływ przedłużających się okresów występowania wysokich temperatur letnich na podejście do projektowania podłogi na gruncie w budynkach mieszkalnych w krajach klimatu umiarkowanego - Staszczuk, Anna; Kuczyński, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The effects of changes in Global climate on the prolonging time and the frequency of the periods of very high outside air temperature at summer were shown in the paper with particular emphasis on European moderate climate countries. In these countries, residential buildings, are usually equipped neither in air conditioning equipment, nor in ordinary window blinds. As the most promising solution it is suggested to resign completely or partially from ground slab thermal insulation, directly utilizing ground heat storage capacity.
Keywords: zmiany klimatu; fale upałów; izolacja ciepła w gruncie; podłoga na gruncie; zapotrzebowanie na chłód; climate changes; heat waves; heat insulation in the ground; thermal insulation; energy consumption; cooling demand